Systematic review and meta‐analysis of optimal initial fraction of oxygen levels in the delivery room at ≤32 weeks. (21st May 2014) - Saugstad, Ola Didrik; Aune, Dagfinn; Aguar, Marta; Kapadia, Vishal; Finer, Neil; Vento, Maximo
Abstract Aim The optimal initial fraction of oxygen (iFiO2) for resuscitating/stabilising premature infants is not known. We aimed to study currently available information and provide guidelines regarding the iFiO2 levels needed to resuscitate/stabilise premature infants of ≤32 weeks' gestation. Methods Our systematic review and meta‐analysis studied the effects of low and high iFiO2 during the resuscitation/stabilisation of 677 newborn babies ≤32 weeks' gestation. Results Ten randomised studies were identified covering 321 infants receiving low (0.21–0.30) iFiO2 levels and 356 receiving high (0.60–1.0) levels. Relative risk for mortality was 0.62 (95% CI: 0.37–1.04, I2 = 0%, pheterogeneity = 0.88) for low versus high iFiO2 ; for bronchopulmonary dysplasia, it was 1.11 (95% CI: 0.73–1.68, I2 = 46%, pheterogeneity = 0.06); and for intraventricular haemorrhage, it was 0.90 (95% CI: 0.53–1.53, I2 = 9%, pheterogeneity = 0.36). Conclusion These data show that reduced mortality approached significance when a low iFiO2 (0.21–0.30) was used for initial stabilisation, compared to a high iFiO2 (0.60–1.0). There was no significant association for bronchopulmonary dysplasia or intraventricular haemorrhage when comparing low and high iFiO2. Based on present data, premature babies ≤32 weeks' gestation in need of stabilisation in the delivery room should be given an iFiO2 of 0.21–0.30.